Modulation of the effects of a cholesterol-supplemented high-fat diet by aryl hydrocarbon receptor (AHR) activation and/or tryptophan reduction in male mice - Bathina, Avinash; Hakanen, Janne; Raasmaja, Atso; Lindén, Jere; Mairinoja, Laura; Unniappan, Suraj; Pettersson, Lars; Pohjanvirta, Raimo (Elsevier BV, 2026)
Aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor whose role in energy metabolism is obscure. Most of its physiological ligands are derived from tryptophan (TRP). Here, fifty male C57BL/6JRccHsd mice were assigned to one of five feeding groups, control diet (CD), high-fat diet (HFD; 45 % of energy from fat), HFD with only 70 % of the regular TRP concentration (HFDtrp), HFD supplemented with a weakly toxic AHR agonist C2 (HFDc2), or HFDtrp with C2 (HFDtrp-c2). All diets contained 2 % cholesterol and were fed for 18 weeks. On weeks 14-16, the mice were tested for gas exchange and locomotor activity, and on weeks 15-17 for glucose tolerance (GTT) and insulin sensitivity (ITT). At termination, tissue samples were collected for biochemical and AI-assisted histological analyses. Body weight gain (BWG) was only 28-38 % higher in the HFD groups than in the CD group, but the HFD-fed mice accumulated 43-61 % more fat. Calorie intake was greater in the two low-TRP groups than in the two other HFD groups, while BWG remained similar. C2 induced Cyp1a1 expression (an index of AHR activity) in all tissues examined and increased the ratio of micro-/macrosteatosis in the liver. The HFDs tended to reduce insulin sensitivity, CO2 production, and the ability to respond appropriately to a low-temperature challenge. These findings suggest that the effects of AHR activity modulation on energy balance are strongly context-dependent. A sensitive response to long-term AHR activation appears to be elevated micro-/macrosteatosis ratio in the liver when exposed to HFD.